2011
DOI: 10.2478/s11535-011-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Trichophyton rubrum manipulates the innate immune functions of human keratinocytes

Abstract: Evasion or subversion of host immune responses have been shown for a variety of microorganisms, and this might be the case for Trichophyton rubrum, the most common pathogenic fungus causing chronic dermatophytosis in humans. Keratinocytes, the main epidermal cells, have important roles as a first defense against microbial challenges in local immune reactions. Epidermal keratinocytes express several Toll-like receptors and produce host defense peptides, cytokines and chemokines in response to various stimuli. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
0
16
0
3
Order By: Relevance
“…GARCÍA-MADRID et al (2011) showed that keratinocytes can recognize and respond to cell wall components of T. rubrum . Viable intact conidia inhibited TLR2 and TLR6 expression by cultured human keratinocytes while conidial homogenate from T. rubrum increased the expression of TLR2, TLR4 and TLR6 7 . Recently, YUKI et al 27 demonstrated that TLR2 activation enhances tight junctions among keratinocytes, a crucial step in maintaining the functional activity of epidermal barriers against infective agents, such as bacteria or fungi.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…GARCÍA-MADRID et al (2011) showed that keratinocytes can recognize and respond to cell wall components of T. rubrum . Viable intact conidia inhibited TLR2 and TLR6 expression by cultured human keratinocytes while conidial homogenate from T. rubrum increased the expression of TLR2, TLR4 and TLR6 7 . Recently, YUKI et al 27 demonstrated that TLR2 activation enhances tight junctions among keratinocytes, a crucial step in maintaining the functional activity of epidermal barriers against infective agents, such as bacteria or fungi.…”
Section: Discussionmentioning
confidence: 90%
“…About 90% of chronic dermatophyte infections are caused by T. rubrum and T. mentagrophytes 8 , 9 , possibly because these organisms may suppress inflammation and cell-mediated immunity 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that Trichophyton rubrum interacts with TLR2 and TLR4 on antigen-presenting cells and promotes cytokines production ( 30 ), we evaluated the relevance of TLR2 and TLR4 in the production of inflammatory mediators induced by T. interdigitale EVs. We stimulated BMDMs obtained from WT, TLR2 −/− , or TLR4 −/− mice with T. interdigitale EVs for 48 h and quantified the levels of TNF-α and IL-6 in the cell supernatants.…”
Section: Resultsmentioning
confidence: 99%
“…Os TLRs 2 e 4 foram descritos na resposta imune às doenças fúngicas, participando da eliminação do patógeno e na imunomodulação da resposta de defesa do hospedeiro (Romani, 2004). Estudo recente em cultura de células mostrou que apesar de homogeneizados de parede fúngica serem capazes de aumentar a expressão de alguns TLRs, conídeos com parede íntegra falharam em fazê-lo (García-Madrid et al, 2011). Com intuito de verificar a expressão epidérmica destes receptores durante a infecção em indivíduos com dermatofitoses, desenhou-se este estudo.…”
Section: Discussionunclassified